2018
DOI: 10.1113/ep087398
|View full text |Cite
|
Sign up to set email alerts
|

Plasma asymmetric dimethylarginine concentrations are not related to differences in maximal oxygen uptake in endurance trained and untrained men

Abstract: New Findings What is the central question of this study?Is there an association of plasma concentration of asymmetric dimethylarginine, which is related to exercise capacity in patients with cardiovascular diseases, with oxygen delivery and subsequently exercise capacity in healthy subjects in the absence of the potentially confounding influence of inflammation and oxidative stress? What is the main finding and its importance?Plasma asymmetric dimethylarginine concentrations are not related to exercise capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
6
2
Order By: Relevance
“…Ilic et al [ 18 ] reported that after exercise stress echocardiography plasma levels of ADMA and SDMA increased both in patients with CAD and in healthy volunteers, with a higher baseline and post-exercise value in the CAD group. In contrast to that, the results of Pawlak-Chaouch et al [ 19 ] did not demonstrate any change in SDMA and ADMA after a maximal graded exercise test in healthy men independently of their physical capacity. Plasma ADMA and SDMA were not associated with the pattern of local muscle deoxygenation and exercise capacity.…”
Section: Discussionmentioning
confidence: 71%
“…Ilic et al [ 18 ] reported that after exercise stress echocardiography plasma levels of ADMA and SDMA increased both in patients with CAD and in healthy volunteers, with a higher baseline and post-exercise value in the CAD group. In contrast to that, the results of Pawlak-Chaouch et al [ 19 ] did not demonstrate any change in SDMA and ADMA after a maximal graded exercise test in healthy men independently of their physical capacity. Plasma ADMA and SDMA were not associated with the pattern of local muscle deoxygenation and exercise capacity.…”
Section: Discussionmentioning
confidence: 71%
“…The levels of ADMA and SDMA are increased in renal failure, but also in subject with cardiovascular disease (CVD) without decreased eGFR [60]. During exercise, the production of NO is increased due to the shear stress in vascular walls [57,61]. Increased levels of NO result in smooth muscle and vascular relaxation [58].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of NO result in smooth muscle and vascular relaxation [58]. Exercise capacity is positively associated with NO-dependent endothelial function in patients with CVD [54,61]. ADMA decreases blood muscle supply during exercise [54,61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations